First New Zealand record of the genus Macrolophus Fieber, 1858 (Hemiptera: Miridae: Bryocorinae: Dicyphini): Macrolophus pygmaeus (Rambur, 1839), a beneficial predacious insect - Eyles, A. C.; Marais, T.; George, S. (Zootaxa, 2008)
Macrolophus pygmaeus (Rambur, 1839) is recorded for the first time in New Zealand. Viable adult M. pygmaeus were collected in the field in Auckland, in 2007, indicating that the species had already established itself in this country. The biology of M. pygmaeus is briefly discussed in the light of its potential economic benefits to growers of vegetable crops affected by whitefly (Aleyrodidae). The adults and nymphs are described and illustrated. An updated key to the genera and species of Bryocorinae in New Zealand is provided.